Fluorescent photoswitchable diarylethenes for biolabeling and single-molecule localization microscopies with optical superresolution - Roubinet, Benoît; Hell, Stefan (Journal of the American Chemical Society, 2017)
A modular assembly of water-soluble diarylethenes (DAEs), applicable as biomarkers for optical nanoscopy, is reported. Reversibly photoswitchable 1,2-bis(2-alkyl-6-phenyl-1-benzothiophene-1,1-dioxide-3-yl)perfluorocyclopentenes possessing a fluorescent “closed” form were decorated with one or two methoxy group(s) attached to the para-position(s) of phenyl ring(s) and two, four, or eight carboxylic acid groups. Antibody conjugates of these DAEs feature low aggregation, efficient photoswitching in aqueous buffers, specific staining of cellular structures, and photophysical properties (high emission efficiencies and low cycloreversion quantum yields) enabling their application in superresolution microscopy. Images of tubulin, vimentin, and nuclear pore complexes are presented. The superresolution images can also be acquired by using solely 488 nm light without additional photoactivation with UV light. These DAEs exhibit reversible photoswitching without requiring any additives to the imaging media and open new paths toward the modular design of fluorescent dyes for bioimaging with optical superresolution.